Research notes on the prevalence and ovipositional tendency of forensically important scuttle fly (Diptera: Phoridae) found in an urban area in Malaysia - Tan, Yap Hoon; Raja Muhammad Zuha,; Baharudin Omar, (penerbit ukm, 2012)
Phorid flies play an important role in forensic cases and can cause myiasis in humans. Studies on phorid flies species diversity are still limited in Malaysia. This research was carried out to collect information about species and frequency distribution of phorid flies as to provide more information on their roles in forensic and medical entomology. Bait trap was used with 100 g beef liver as baits. The species of the flies were identified using identification keys from Disney as well as Brown and Oliver. There were 449 phorid flies found in Kepong, Kuala Lumpur including Megaselia scalaris, Megaselia spiracularis, Megaselia sp. and phorid flies of genus X. Female phorid flies (98.89%) were found more prone to be trapped compared to male phorid flies (1.11%). Most phorid flies trapped in Kepong, Kuala Lumpur were from genus Megaselia and consisted of female flies. A total of five species of phorid flies probably new to science were also discovered. This study showed that Megaselia flies were found indoors rather than in open spaces. This was corresponding to their discoveries among the decomposing corpse found inside premises.